A Concise Approach Toward Tetrazolyl-Substituted Benzazocines via a Novel Isocyanide-Based Multicomponent Reaction - Borisov, Roman S.; Voskressensky, Leonid G.; Polyakov, Anatoly I.; Borisova, Tatiana N.; Varlamov, Alexey V. (Synlett, 2014)
The synthesis of pharmacologically relevant isoquinoline-tetrazoles and benzazocine-tetrazoles via sequential azido-Ugi and alkyne-induced ring-expansion reactions starting from cotarnine chloride are reported. A one-pot, multicomponent reaction protocol toward the ring-expanded product is also described.
Keywords: alkaloids; multicomponent reaction; domino reaction; ring expansion; alkynes